Post-colonial theory and English literature : a reader (Edinburgh University Press, 1999)
Includes critical essays on William Shakespeare's The Tempest; Daniel Defoe's Robinson Crusoe; Charlotte Bronte's Jane Eyre; Joseph Conrad's Heart of Darkness; Rudyard Kipling's Kim; James Joyce's Ulysses; E.M. Forster's A passage to India; and, Salman Rushdie's The satanic verses.